2019
DOI: 10.1149/2.0091915jes
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Thrombin Detection by Combination of Click Chemistry and Surface-Initiated Polymerization

Abstract: Thrombin has a strong correlation to a variety of diseases, and it is of great significance to improve the sensitivity of thrombin detection. Herein, we report a biosensor for highly sensitive thrombin detection (17 fM) by combination of click chemistry and surface-initiated atom transfer radical polymerization (SI-ATRP). A sandwich structure is formed among thiol-modified aptamer-1, thrombin and azido-labeled aptamer-2. Then the initiators of SI-ATRP (propargyl α-bromoisobutyrate, PBiB) can be introduced to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These include, for example, modifying probe density, 61 the nature of the blocking monolayer, 62 the redox reporter 63 and the microscopic architecture of the electrode, 64,65 the electrode surface area to increase the moles of DNA receptors, [66][67][68][69] coupling a catalytic process to electron transfer events to amplify binding-induced signals 43,70 or achieving binding-induced receptor polymerization to also amplify signaling. 71 Computational methods have also been reported that achieve lower detection limits via noise processing strategies. 72 Although the ultimate limit of detection is inherently set by the receptor K D and signal amplification mechanism, it can also be improved via a The vast majority of DNA-based sensors use the redox couple methylene blue/leucomethylene blue, which has a k 0 significantly slower than that for ferrocenes or other commonly used redox reporters.…”
Section: Shape Of the Calibration Curve And Limits Of Detectionmentioning
confidence: 99%
“…These include, for example, modifying probe density, 61 the nature of the blocking monolayer, 62 the redox reporter 63 and the microscopic architecture of the electrode, 64,65 the electrode surface area to increase the moles of DNA receptors, [66][67][68][69] coupling a catalytic process to electron transfer events to amplify binding-induced signals 43,70 or achieving binding-induced receptor polymerization to also amplify signaling. 71 Computational methods have also been reported that achieve lower detection limits via noise processing strategies. 72 Although the ultimate limit of detection is inherently set by the receptor K D and signal amplification mechanism, it can also be improved via a The vast majority of DNA-based sensors use the redox couple methylene blue/leucomethylene blue, which has a k 0 significantly slower than that for ferrocenes or other commonly used redox reporters.…”
Section: Shape Of the Calibration Curve And Limits Of Detectionmentioning
confidence: 99%
“…Thrombin (TB) plays a significant role in diseases such as thromboembolic disease, leukemia, and inflammatory reactions. 1,2 To address global health concerns, particularly in developing countries, it is highly desirable to develop cost-effective and efficient methods for the quantitative detection of thrombin. Traditional protein analysis methods, such as enzyme-linked immunosorbent assays, western blots, and polarization assays, encounter limitations due to expensive equipment and complex procedures, restricting their use in routine clinical diagnostics.…”
mentioning
confidence: 99%
“…3 The concentration of TB in the blood can vary from nanomolar to micromolar, and the high or low concentration of TB is associated with various diseases such as thromboembolic disease, hemophilia and Alzheimer's disease. 4,5 Notably, TB is a biomarker for cardiovascular disease and tumor diagnosis of pulmonary metastasis. 6 As a consequence, development a reliable and sensitive analytical method for TB detection is very urgent and important to the pubilc health.…”
mentioning
confidence: 99%
“…Multiple detection methods have been designed for TB aptasensing, including colorimetric assay, 8 fluorescence analysis, 9 surfaceenhanced raman scattering, 10 resonance rayleigh scattering, 11 and electrochemical approach. 5,12,13 Among all these methods, TB electrochemical aptasensors proved to be an excellent method for TB detection due to the low cost, simplicity and high sensitivity. Enzyme 14 and redox dye 15,16 such as methylene blue was usually used as signal probes for TB electrochemical aptasensors.…”
mentioning
confidence: 99%